The Crime Novel in 21st-Century Central America: Two Novels by Gerardo Guinea Diez - López Martínez, María del Pilar (2023)
This article proposes aspects for the characterization of the crime novel in the Central American region and its expansion as a category generally linked to the police or Noir, based on the study of aesthetic writing that presents cases of genocide in current societies. It addresses two Guatemalan novels from the beginning of the 21st century written by Gerardo Guinea Diez: El árbol de Adán and La mirada remota. It applies theoretical concepts from Segato, Bourdieu, Arendt and Agamben, for the analysis of fundamental categories such as those of nation, state, democracy, citizenship or freedom.